2021
DOI: 10.1002/nop2.836
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bed bath methods for skin integrity, skin cleanliness and comfort enhancement in adults: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…Os achados de uma revisão sistemática evidenciaram que a aplicação de uma toalha quente na pele dos pacientes antes de iniciar o banho assegura o fornecimento de calor, sendo uma intervenção útil para evitar a redução da temperatura corporal e para promover maior conforto dos pacientes submetidos ao banho no leito. (15) Além disso, não se pode ignorar que a temperatura axilar pode sofrer influências de variáveis como idade, frequência cardíaca, pressão arterial e temperatura ambiental. (16) Assim, torna-se importante que o cuidado seja realizado de modo individualizado, levando-se em consideração as questões individuais e ambientais.…”
Section: Discussionunclassified
“…Os achados de uma revisão sistemática evidenciaram que a aplicação de uma toalha quente na pele dos pacientes antes de iniciar o banho assegura o fornecimento de calor, sendo uma intervenção útil para evitar a redução da temperatura corporal e para promover maior conforto dos pacientes submetidos ao banho no leito. (15) Além disso, não se pode ignorar que a temperatura axilar pode sofrer influências de variáveis como idade, frequência cardíaca, pressão arterial e temperatura ambiental. (16) Assim, torna-se importante que o cuidado seja realizado de modo individualizado, levando-se em consideração as questões individuais e ambientais.…”
Section: Discussionunclassified
“…Systematic reviews are carried out in accordance with the preferred reporting items for systematic review and meta-analysis and the Joanna Briggs Institute Reviewer's Manual that this protocol is not listed in any database before [5]. The inclusion and exclusion criteria using the PICOS format (JBI, 2020) are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…However, this method is limited such that the degree of contamination prior to data collection cannot be standardized because of the frequency of skin care and associated skin contamination of the patient, which may not allow for precise evaluation. Therefore, methods for intentionally applying dirt and evaluating the removal rate have been used to precisely evaluate the degree of dirt removal based on differences in wiping methods [ 9 , 13 ]. Thus, this study visualized skin cleanliness using colour image analysis according to previous methods [ 11 ].…”
Section: Study 2: Methodsmentioning
confidence: 99%
“…Although the use of cotton and disposable towels has been reported at 71.0% and 12.2%, respectively [ 27 ], disposable towels became the first choice in bed baths for infected patients [ 28 ] during the COVID-19 pandemic. Moreover, two systematic reviews have shown that disposable wipes are no less effective than cotton wipes in preventing skin lesions and removing bacteria in older adults [ 13 , 26 ]. Furthermore, disposable wipes have been shown to be a valuable alternative to cotton wipes in terms of comfort of the care recipients [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation